EFFECT OF GROWTH REGULATORS AND CORM SIZE ON GROWTH AND CORM PARAMETERS IN GLADIOLUS CV. MALAVIYA KUNDAN - SAIPRIYA PANIGRAHI,; ANJANA SISODIA,; ANIL K. SINGH, (The Bioscan, 2020)
A field experiment on gladiolus cv. Malaviya Kundan consisted of thiourea 0.5%, thiourea 1.5%, thiourea 2.0%, GA 3 50 ppm, GA 3 100 ppm, GA 3 150 ppm, control and four levels of corm sizes (1.0, 1.5, 2.0, 2.5 cm) in a Randomized Block Design. GA 3 at 150 ppm recorded significantly maximum number of leaves/plant (4.76), plant height (39.70 cm), length of longest leaf (37.35 cm) at 60 days after planting (DAP), weight of corms/hill (17.60 g) and diameter of corm (3.43 cm). Whereas, thiourea at 1.5% resulted maximum number of cormels/hill (42.98) and weight of cormels/hill (5.90 g). Among various grades of corm grade 2.5 cm recorded maximum number of leaves/plant (4.63) at 60 DAP, number of corms/hill (1.07), weight of corms/hill (18.74 g) and diameter of corm (3.50 cm). Whereas, corm size 2.0 cm resulted maximum plant height (39.83 cm), length of longest leaf (35.11 cm) at 60 DAP, number of cormels/hill (37.31) and weight of cormels/hill (5.75 g). Whereas, interaction of GA 3 150 ppm with corm size 2.5 cm recorded maximum number of leaves/plant (5.00), plant height (42.26 cm) and length of longest leaf (39.86 cm) at 60 DAP, weight of corms/hill (24.03 g) and diameter of corms/hill (3.84 g).